MORE SEWING TO SELLTAKE YOUR HANDMADE BUSINESS TO THE NEXT LEVEL 16 new projects to make & sell! - LINDSAY, VIRGINIA ([s.n], WATSON-GUPTILL, 2018)
Take your handmade business to a truly professional level with practical advicefrom industry experts!
1
Keywords: sewing